The use of methotrexate in conservative treatment of placenta accreta spectrum disorders. (12th December 2022) - Gregoir, Caroline; De Becker, Ben; Hauspy, Jan; Vanderheyden, Tina; Loquet, Philip
Abstract: Aim of the study: This article reports on a series of patients with placenta accreta spectrum (PAS) disorder who were treated conservatively with Methotrexate (MTX) administration with or without embolization. We investigate whether there is a place for MTX in conservative treatment of PAS. Methods: We present a single-center retrospective case series of five patients. In all patients, diagnosis was unexpected and not made prenatally. Conclusion: The benefits should be weighed against the possible drug toxicity. Today high-quality evidence is lacking. PAS covers a broad spectrum of pathology, standardization in prenatal and postnatal diagnosis can help to compare evidence on treatment.